Right ventricular upregulation of the Ca2+ binding protein S100A1 in chronic pulmonary hypertension - Ehlermann, Philipp; Remppis, Bjoern-Andrew; Guddat, Oliver; Weimann, Jörg; Schnabel, Philipp Albert; Motsch, Johann; Heizmann, Claus W.; Katus, Hugo (Biochimica et biophysica acta. Molecular basis of disease, 2000)
The Ca2+ binding protein S100A1 increases the Ca2+ release from the sarcoplasmatic reticulum by interacting with the ryanodine receptor. In order to understand whether this effect might be operative in the early course of hypertrophy, when myocardium is able to meet increased workload, we investigated the expression of S100A1 in a model of moderate right ventricular hypertrophy. The pulmonary arteries of nine pigs were embolised three times with Sephadex G-50. After 70 days, all pigs showed a moderate pulmonary hypertension. Right ventricular tissue of embolised animals showed a significant increase of connective tissue and enlargement of myocyte diameters. In controls, we found a differential expression of S100A1 with significantly lower S100A1 protein levels in right ventricular compared to left ventricular tissue. In pulmonary hypertension, S100A1 expression increased significantly in hypertrophied right ventricles while it was unchanged in left ventricular tissue. No change was observed in the expression of SERCA2a and phospholamban. Our data show, for the first time, that moderate pressure overload results in an upregulation of S100A1. This may reflect an adaptive response of myocardial Ca2+ homeostasis to a higher workload.